A new non-isidiate Leptogium species with transverse septate ascospores from Southeastern Brazil - Kitaura, Marcos Junji [UNESP]; Marcelli, Marcelo Pinto; Hora, Bianca Regina da [UNESP]; Jungbluth, Patrícia [UNESP] (My University, 2013)
A non-isidiate Leptogium species with transverse septate ascospores is described as new. The species was collected in Serra da Mantiqueira and initially identified as L. megapotamicum, but the study of the type specimen demonstrated differences in the tissues of the apothecia, which supported the observed morphological variations of the thalli and apothecia found by our descriptive protocol.
Keywords: Amphithecia; Columnar hyphae; Section Leptogiopsis; Subhymenial tissue